Executive Functions in Clinical and Non-Clinical Populations. A Comparative Analysis - Dana A. ICLOZAN; Iulia F. POP (Studia Universitatis Babes-Bolyai, 2024)
The primary aim of the study was to assess and compare executive functions in psychiatric inpatients (n=65) with those of a matched control group of healthy individuals (n=65). Both cohorts underwent rigorous evaluation using neuropsychological performance-based tests and self-assessment scales. Findings indicated a superior performance by the control group in both self-assessed and computerized evaluations. Notably, there was an absence of correlation between results from the performance-based test (Corsi) and self-assessments of executive function. Subsequent analysis focusing on primary diagnostic categories highlighted that patients diagnosed with depression consistently undervalued their performance in the self-assessment as opposed to the objective, computer-based evaluations. This undervaluation was observed across total scores and individual subscales. In contrast, patients diagnosed with alcohol dependence exhibited a tendency to overestimate their performance in self-assessments relative to the objective tests. The study investigates the causes of these observed differences and considers their implications for subsequent research and clinical practices.